PENERAPAN PAJAK INTERNASIONAL DI INDONESIA - Dian Nadya Novarina; Iis Rohayati (CV. Adiba Aisha Amira, 2024)
International tax is a dynamic and evolving field, which is greatly influenced by changes in the global economy, policy, and technology. Effective handling of issues arising from international tax requires cooperation and coordination between countries, as well as adaptation to changes in the economic and technological environment. This new international tax system is in line with the spirit of national tax reform, which among other things aims to increase the tax base fairly. For emerging countries like Indonesia, this is important to optimize its domestic revenue sources. The cause of the low and continuing decline in Indonesia's tax to GDP ratio is the inability of the tax system to capture the increase in economic activity, one of which is due to BEPS (Base Erosion Profit Shifting). Indonesia's international tax rules, which relate to international trade activities such as imports and exports, are limited to tax subjects and objects located in Indonesian territory. However, this also relates to subjects and objects outside the territory of Indonesia that have close economic and state relations with the country. Indonesia's national tax law, particularly in terms of agreements to avoid double taxation and prevention of tax evasion, is reflected in the Income Tax Law.